LB15. Vaccine Effectiveness of Flucelvax Relative to Inactivated Influenza Vaccine During the 2017–18 Influenza Season in Northern California. (26th November 2018) - Klein, Nicola P; Fireman, Bruce; Goddard, Kristin; Zerbo, Ousseny; Asher, Jason; Zhou, James; King, James; Lewis, Ned
Abstract: Background: In June 2018, the CDC reported that influenza vaccine effectiveness (VE) against A(H3N2) influenza virus for the 2017–2018 season was 24%. This lower than expected VE was hypothesized to be partially related to genetic changes arising in the vaccine virus during passage in eggs. Flucelvax™ (Seqirus) is a cell culture-based inactivated influenza vaccine (ccIIV) which is not manufactured in eggs. We investigated whether the VE of ccIIV against influenza A differed from that of egg-based IIV (ebIIV) during the 2017–2018 influenza season. Methods: The study included all Kaiser Permanente Northern California members aged 4–64 years. We identified all individuals who were positive for influenza by polymerase chain reaction (PCR). This cohort analysis estimated the relative VE of ccIIV vs. ebIIV by comparing the ccIIV vaccinees vs. the ebIIV vaccinees with respect to the risk of PCR-confirmed influenza. We separately estimated the absolute VE of ccIIV and ebIIV by comparing each group of vaccinees with unvaccinated individuals. We used Cox regression with a calendar timeline, stratified by birth year, and adjusted for facility, race, years of membership, prior season influenza vaccine, co-morbidities, and number of inpatient admits in the prior year. We calculated VE as 1 − hazard ratio (HR). Results: Of the 3, 015, 891 members aged 4–64 years, 1, 017, 314 were vaccinated. Of these, 932, 874 (91.7%) received ebIIV and 84, 440 (8.3%) received ccIIV. Most ebIIV (86.2%) was trivalent. Comparing ccIIV with ebIIV, the adjusted relative VE against influenza A was 6.8% (95% CI: 11.2, 21.9; P = 0.43). The adjusted absolute VE vs. unvaccinated of ccIIV was 30.2% (95% CI: 17.1, 41.3; P < 0.0001) and of ebIIV was 17.9% (95% CI: 12.1, 23.3; P < 0.0001). Conclusion: Both cell-culture and egg-based IIV vaccines showed relatively low effectiveness during the 2017–2018 influenza season in which A(H3N2) predominated. The findings of this study show there was no significant difference in the effectiveness of cell-culture IIV compared with egg-based IIVs. Improvements in influenza vaccines will require ongoing monitoring of vaccine effectiveness. Disclosures: N. P. Klein, GSK: Investigator, Research support. Sanofi Pasteur: Investigator, Research support. Merck: Investigator, Research support. Pfizer: Investigator, Research support. Protein Science: Investigator, Research support. MedImmune: Investigator, Research support. Dynavax: Investigator, Research support.